Unequal Frames: Minority Coverage of Student Media in Indonesia and the Philippines - Ramos, Laurence Lingat; Anshori, Mahfud (Jurnal Kajian Jurnalisme, 2026)
Background: Decades of media content reveal that framing serves as a primary mechanism for the social transmission of bias, directly contributing to formation and solidification of harmful minority stereotypes. This concern is particularly urgent in student media, which functions as a foundational training ground where student journalists develop reporting habits and cognitive schemas that may carry into their professional careers. Purpose: The study explored how minority groups framed in student media of state universities in Indonesia (Balairung UGM) and the Philippines (CLSU Collegian) specifically their periodical issues from 2020 to 2024. Methods: Using qualitative content analysis, twelve stories have been examined using Framing Theory, these stories were identified using Wirth’s (1945) definition of a minority group as criterion. Results: Study revealed that student media in the Philippines uses relative cultural openness to foreground gender-related narratives. Conversely, Indonesian student media demonstrates an absence in coverage, reflecting severe legal/cultural constraints that reinforce heteronormativity and restrict visibility. While CLSU Collegian frames disability as a rights-based struggle (policy-conscious critique paired with individual success). Balairung UGM frames it as spiritually mediated experience, prioritizing faith-centered recovery and collective care within localized cultural practices, also frames Indigenous People through systems, depicting them either as victims of state-led development or as ecological exemplars. Philippine student media emphasizes personal journeys and inclusion, centering IP students' resilience, cultural assertion, and myth-breaking within higher education. Conclusion: The study concludes that Philippine student media frames minority stories emphasizing individual agency and rights, contrasting with Indonesian media focusing on structural conditions and collective frameworks. This reflects a national split between visibility and constraint. Implications: This study implies that journalism education should address unconscious framing biases in student media, while policymakers and institutions work to ease the legal and cultural constraints that shape minority visibility and push coverage toward greater structural accountability.